A Predictive Genetic Signature for Response to Fluoropyrimidine-Based Neoadjuvant Chemoradiation in Clinical Stage II and III Rectal Cancer - Chan, Jason; Kinsella, Michael; Willis, Joseph; Hu, Huankai; Reynolds, Harry; Delaney, Conor; McCulla, Andrea; Deharo, Steve; Ahdesmaki, Miika; Allen, Wendy L.; Johnston, Patrick; Kinsella, Timothy J. (Frontiers in Oncology, 2013)
Purpose Preoperative chemoradiation is currently the standard of care for patients with clinical stage II and III rectal cancer but only about 45% of patients achieve tumor downstaging and less than 20% of patients achieve a pathologic complete response. Better methods to stratify patients according to potential neoadjuvant treatment response are needed. We used microarray analysis to identify a genetic signature that correlates with a pathological complete response to neoadjuvant chemoradiation. We performed a gene network analysis to identify potential signaling pathways involved in determining response to neoadjuvant treatment. Patients and Methods We identified 31 T3-4 N0-1 rectal cancer patients who were treated with neoadjuvant fluorouracil-based chemoradiation. 8 patients were identified to have achieved a pathological complete response to treatment while 23 patients did not. mRNA expression was analyzed using cDNA microarrays. The correlation between mRNA expression and pathological complete response from pre-treatment tumor biopsies was determined. Gene network analysis was performed for the genes represented by the predictive signature. Results A genetic signature represented by expression levels of the 3 genes EHBP1, STAT1, and GAPDH was found to correlate with a pathological complete response to neoadjuvant treatment. The difference in expression levels between patients who achieved a pathological complete response and those who did not was greatest for EHBP1. Gene network analysis showed that the 3 genes can be connected by the gene UBC. Conclusion This study identifies a 3-gene signature expressed in pre-treatment tumor biopsies that correlates with a pathological complete response to neoadjuvant chemoradiation in patients with clinical stage II and III rectal cancer. These 3 genes can be connected by the gene UBC, suggesting that ubiquination is a molecular mechanism involved in determining response to treatment. Validating this genet